Environmental effectiveness of GAEC cross-compliance Standard 4.2 on biodiversity in set-aside management and economic evaluation of the competitiveness gap for farmers, part I - Mocali, Stefano; Landi, Silvia; Fabiani, Arturo; Piccolo, Raimondo; Agnelli, Alessandro; d'Errico, Giada; Mazza, Giuseppe; Fedrizzi, Marco; Sperandio, Giulio; Guerrieri, Mirko; Pagano, Mauro; Puri, Daniele; et al. (Italian Journal of Agronomy, 2016)
In 2005, the CAP reform introduced the principle of conditionality that enables the access to single payments for farmers only ‘on condition’ that a series of commitments, such as the Statutory Management Requirements (SMR) and Good Agricultural and Environmental Conditions (GAEC), are respected. In particular, the GAEC Standard 4.2 aims to ensure the proper management of the set-aside fields through specific agronomic practices consisting in mowing or equivalent operations in order to conserve and protect biodiversity. This is considered one of the main environmental challenges of the new CAP. In the present work, we report the results of a monitoring activity aimed at evaluating the effectiveness of the Standard 4.2 on soil biodiversity. Monitoring involved both, soil microorganisms and soil arthropod fauna, representing the so-called ‘invisible biodiversity’, a key element for soil fertility and sustainability, as well as the ground-dwelling arthropods. Two different managements of set-aside, with and without mowing, were compared in three different areas in Italy: Caorle (VE), Fagna (FI), and Metaponto (MT). The results showed a slight but significant increase in biodiversity in the plots where mowing was applied.